Development Of An Enzyme-Linked Aptasorbant Assay In Detecting Dengue Virus 2 Ns1 Biomarker - Ramesh, Thevendran (2022)
Dengue is an alarming threat to both the health and economy of multiple nations worldwide. However, the current approaches used in the diagnostic application of dengue virus infections are limited to antibodies-based techniques which concurrently possess several disadvantages. Aptamers are a class of folded nucleic acid strands capable of binding to different cognate target molecules with high affinity and selectivity. Aptamers alleviate the drawbacks of antibodies by facilitating as cost-effective and efficient analytical tools in identifying dengue infections.